The Role of Variance Analysis as a Project Costs Controlling Tool - Hikmahwati; Aliffa Yulianti Muslimah (Jurusan Akuntansi Politeknik Negeri Malang, 2023)
The Role of Variance Analysis as a Project Costs Controlling ToolPurpose: To analyse the role of variance analysis as a cost control tool for controlling project costs which was implemented during the Covid-19 pandemic. Method: Quantitative with a case study approach. Result: Variance analysis can be used as a cost control tool for Road Rehabilitation projects during the Covid-19 pandemic. Using variance analysis, it can be seen that the existence of the Covid-19 pandemic has affected the company's operating costs, indicated by the presence of unfavorable and favorable projects. Novelty: Variance analysis can be used to identify areas where project cost deviations occurred during the Covid-19 pandemic. Contribution: Management can use variance analysis to anticipate significant cost changes in the construction sector Peran Analisis Varians Sebagai Alat Pengendalian Biaya ProyekTujuan: mengkaji peran analisis varians sebagai alat pengendalian biaya proyek yang pelaksanaannya terjadi pada pandemi Covid-19. Metode: Kuantitatif dengan pendekatan studi kasus. Hasil: Variance analysis bisa digunakan sebagai alat pengendalian biaya proyek Rehabilitasi Jalan pada saat pandemic Covid-19. penggunaan variance analisis dapat dilihat bahwa keberadaan Pandemi Covid-19 telah memengaruhi biaya operasional perusahaan, ditunjukkan dengan adanya varians tidak menguntungkan dan menguntungkan dalam pelaksanaan proyek. Kebaruan: Analisis varians bisa digunakan sebagai idintifikasi area mana yang terjadinya penyimpangan biaya proyek saat pandemi Covid-19. Kontribusi: Pihak manajemen bisa menggunakan variance analysis untuk mengantisipasi terjadinya perubahan biaya yang signifikan di sektor konstruksi.